Environmental assessment of the beam trawling technique as used in Belgian fishing grounds considering the full lifespan of the vessel - Matthys, Sarah; De Tavernier, Johan; Geeraerd Ameryckx, Annemie (Frontiers in Sustainability, 2026)
Fish is a high-protein food often included in healthy diets. Compared to other animal protein sources, fish generally have lower environmental impacts. However, Life Cycle Assessments (LCAs) quantifying the impacts of wild caught fish most often exclude data inventory on vessel construction and maintenance, commonly without sufficient rationale. This research addressed this gap by first reviewing the 16 previous LCAs on wild caught fish that did consider (some level of) construction and/or maintenance. As a case-study, an LCA was performed for the fishing activities in Belgian fishing grounds by a large beam trawler, the fleet segment responsible for 70% of Belgium's 2020 catch. The system boundaries extended from vessel construction to fish auction, incorporating construction plans, maintenance records, and expert guidance. Results showed that construction and maintenance contributed minimally to climate change, particulate matter, and fossil resource use, justifying omission in LCA studies for long-operating vessels with considerable fuel use. However, this was not true for several impact categories, including water use, toxicity-related impact, eco-toxicity freshwater, eutrophication freshwater, and resource use minerals and metals. These impacts were primarily linked to the vessel's steel, the netting, and the copper cathode. Our findings suggest that while exclusion of construction and maintenance may be justified for certain impact categories, their inclusion is recommended when assessing toxicity and resource-related impacts. When full inventory data are unavailable, representative data on key materials can offer a reasonable approximation. Our study provides suggestions for LCA practitioners to make informed decisions about system boundaries, balancing methodological rigor with practical feasibility.